Двухмодульная система измерения зональной гармоники первого порядка магнитного поля технических объектов - Дегтярёв, А. В. (ХНУРЭ, 2005)
A two-module system of measurement of axial magnetic momentum of technical objects with regulated intensity level of magnetic field is offered. An algorithm for neutralization of the weightiest multiple interferences of space harmonics of magnetic field of object on the measurement results, is obtained. Mathematical models of measured signal and multiple component of mathematical error, are elaborated. The two-module system increases measurement accuracy of axial dipole momentum of magnetic field sources nearby their surface in one order as compared with basic one-module measurement system. Целью исследования является создание совокупности эффективных методов и средств измерения магнитных параметров источников ВМП, которые обеспечивают повышение достоверности результатов контроля электромагнитной обстановки в заданных зонах промышленных, энергетических и других объектов, необходимых для решения ряда практических задач по электромагнитной совместимости и магнитной экологии.
Keywords: контроль электромагнитной обстановки; метрология; экология